Clinical and morphological parallels in preterm birth - Sitnikova, V.; Nadvorna, O.; Rozhkovska, N.; Kashian, O. (Journal of Education, Health and Sport, 2021)
The aim of the study was to establish a link between the timing of preterm birth and clinical groups of women of different ages. There were demonstrated the differences in the incidence of preterm birth among women of different reproductive ages in our study were not found (p>0,05). The rate of cesarean delivery was higher (p>0,05) in women who gave birth from 22 to 27 weeks of gestation. The threatened abortions in the I and II trimesters were observed in women of all groups. In women of the I and II groups the phenomena of placental dysfunction in the form of infarcts and retroplacental hematomas on the background of various urogenital infections were revealed. Indicators of compensatory-adaptive response in the placenta are better developed in women who gave birth at 33-37 weeks. Developmental pathology and location of the umbilical cord occurred in women whose children were born in the terminals from 22 to 33 weeks of pregnancy. Mortality among children at 22-27 weeks was higher in parallel with a higher percentage of cesarean sections in the same group compared to the other two groups.